Pelaksanaan Pembelajaran Geografi Masa Pandemi Covid-19 di SMAN 1 Bungku Tangah Kabupaten Morowali - Ende, Rahma Ylianingsih; Latif, Juraid (Jurusan Pendidikan IPS, Fakultas Keguruan dan Ilmu Pendidikan Universitas Tadulako, 2022)
This study aims to describe the implementation of geography learning during the covid-19 pandemic which includes learning preparation, knowing the evaluations and obstacles experienced by students and teachers, and the efforts made by teachers in implementing learning during the covid-19 pandemic at SMAN 1 Bungku Tengah, Morowali Regency with the type of qualitative descriptive research and using the object of geography subject teachers and students. Data collection using research methods of observation, interviews, and documentation. The results showed that the implementation of geography learning used two methods, namely online and offline. Preparation of online learning by teachers before the implementation of learning during the COVID-19 pandemic begins by preparing appropriate teaching materials in lesson plans, learning videos, ppt and assignments. Online learning ensures the availability of internet services. The implementation of online learning conveys material via zoom, teachers and students use the WhatsApp learning application to send information about learning, materials, learning animation videos, and ppt. While in face-to-face learning, the teacher conducts door-to-door learning, namely visiting students or students coming to teachers to school to carry out learning. The forms of evaluation in the implementation of learning are the duration of the assignment. The problem with online learning is that there are network service disruptions when delivering/receiving material. In contrast, offline learning has obstacles, namely access conditions and the distance from the house that must be taken, resulting in limited learning time. Online and offline learning have different syntaxes. The achievement of learning success at the SMAN 1 Bungku Tengah school is offline learning because it is superior in the ongoing learning process